2011
DOI: 10.4081/vsd.2011.2204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of passive immunization by anti-gingipain IgY on periodontal health of dogs

Abstract: Anti-gingipain IgY (IgY-GP), known as hyperimmune γ-livetin from egg yolk, inhibits the enzyme activity, growth and adherence of <em>Porphyromonas gingivalis</em> to gingival epithelial cells. Our objective was to evaluate the efficacy of IgY-GP on periodontal health of dogs. IgY-GP was prepared from the egg yolk of hens immunized with the gingipain from <em>Porphyromonas gingivalis</em> ATCC 33277. Two <em>in vivo</em> trial models were conducted on 15 adult dogs with perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
7
0
3
Order By: Relevance
“…18,19 Anti-gingipain IgY has a cross-reactivity with the same enzyme expressed by P gulae and protects various cell lines from damages by the enzymes expressed by both P gingivali s and P gulae , and therefore, it is conceivable that this cross-reactivity may have therapeutic potential in cats since it could target other Porphyromonas species commonly found in the oral cavity of cats. 20 Positive results with the use of IgY in the oral health of humans and dogs have been reported, but no studies including cats have been found by the authors. 19,20 The aim of this study was to evaluate the effects of consumption of kibble diet coated with IgY-GP on P gingivalis count, dental plaque index, dental calculus index, and gingivitis index of cats with PD.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…18,19 Anti-gingipain IgY has a cross-reactivity with the same enzyme expressed by P gulae and protects various cell lines from damages by the enzymes expressed by both P gingivali s and P gulae , and therefore, it is conceivable that this cross-reactivity may have therapeutic potential in cats since it could target other Porphyromonas species commonly found in the oral cavity of cats. 20 Positive results with the use of IgY in the oral health of humans and dogs have been reported, but no studies including cats have been found by the authors. 19,20 The aim of this study was to evaluate the effects of consumption of kibble diet coated with IgY-GP on P gingivalis count, dental plaque index, dental calculus index, and gingivitis index of cats with PD.…”
Section: Introductionmentioning
confidence: 98%
“…20 Positive results with the use of IgY in the oral health of humans and dogs have been reported, but no studies including cats have been found by the authors. 19,20 The aim of this study was to evaluate the effects of consumption of kibble diet coated with IgY-GP on P gingivalis count, dental plaque index, dental calculus index, and gingivitis index of cats with PD.…”
Section: Introductionmentioning
confidence: 98%
“…Foram utilizados três grupos, grupo controle sem IgY, gurpo controle com IgY controle, a qual não reagia com nenhuma das Porphyromonas spp e o grupo IgY-PG. A IgY-PG inibiu a atividade proteolítica das preparações de gingipaínas de P. gulae e P. gingivalis em 50% e 60%, respectivamente, levando ao menor dano às células e aumento da sua sobrevivência em comparação ao grupo controle não tratado e o controle que recebeu IgY controle(SHOFIQUR et al, 2011).No estudo in vivo com cães, os animais foram divididos em três grupos com cinco cães cada, um controle, sem administração de IgY, um teste que recebeu 35mg de IgY-PG por kg de peso corporal uma vez ao dia e outro que recebeu 17,5 de IgY-PG por kg de peso corporal duas vezes ao dia, sendo o IgY-PG administrado sobre a alimentação comercial. A média de todos os parâmetros analisados, incluindo gengivite, periodontite, índice de saúde bucal, e sangramento à sonda, foram significativamente menores após 08 semanas, em comparação com a linha de base.…”
unclassified
“…Não houve diferenças notáveis entre os dois grupos teste (Teste 1: 35mg de IgY-PG/kg de peso corporal, uma vez ao dia; Teste 2: 17,5mg de IgY-PG/kg de peso corporal, duas vezes ao dia). Houve diferença significativa na remoção do cálculo dentário entre o grupo Teste 1 e o controle(SHOFIQUR et al, 2011).Na segunda parte do estudo foram utilizados cinco cães e selecionados dois pares de dentes pré-molares contralaterais em cada animal, todos com inflamação gengival clara e profundidade de bolsa ≥ 5mm, um dente de cada contralateral foi tratado com 20% de IgY-PG misturada com pomada odontológica (um gel neutro contendo gel de hidrocarboneto, ésteres de sacarose e hidroxipropilmetilcelulose) e os outros dentes foram tratados somente com apomada odontológica. A pomada foi administrada quatro vezes na semana (200mg/bolsa periodontal/hora) dentro da bolsa periodontal com auxilio de uma seringa.…”
unclassified
See 1 more Smart Citation